Adverse events, resource use, and economic burden associated with mantle cell lymphoma: a real-world assessment of privately insured patients in the United States. Issue 4 (21st March 2019) - Goyal, Ravi K.; Nagar, Saurabh P.; Kabadi, Shaum M.; Kaye, James A.; Seal, Brian; Mato, Anthony R.
Abstract: In view of recent therapeutic advances in mantle cell lymphoma (MCL), the aim of this retrospective cohort analysis was to assess treatment patterns, adverse events (AEs), resource utilization, and health care costs in patients with MCL in a US-based commercial claims database. A total of 783 patients with MCL (median age = 65 years) were selected. Among patients receiving systemic therapy ( n = 457), the most common treatment regimens were bendamustine/rituximab (BR) (41.1%), rituximab/cyclophosphamide/doxorubicin/vincristine (RCHOP) (26.7%), rituximab monotherapy (20.4%), and ibrutinib monotherapy (14.2%). Mean monthly costs during treatments with BR, RCHOP, rituximab, and ibrutinib were 12, 958, 24, 719, 13, 153, and 21, 690, respectively. Mean monthly cost during follow-up was 13, 650 among patients with ≥6 AEs versus 5131 among those without AEs. The costs of MCL varied considerably by treatment regimen and care setting. The overall economic burden of managing patients with MCL can be substantially affected by costs associated with managing AEs occurring during treatment.